Nanosensors - Yupapin, Preecha P.; Teeka, Chat; Jalil, Muhammad Arif; Ali, Jalil (Nanoscale Nonlinear PANDA Ring Resonator, 2012)
Nano-science and technology has become the common subject that introduces many related research areas today. One of them is the nano-scale measurement resolution, i.e. nano metrology which can be used to support and confirm the small scale regime of the observed physical quantities. To date, there are many techniques that can be performed the nano-scale measurement resolutions and standards [1-4], however, the searching for new measurement standards and techniques still remains. Recently, Yupapin and Pornsuwancharoen [5] have shown the interesting result that light pulse can be stretched or compressed and stored within a tiny device known as "nano-waveguide". Several research works have also shown the interesting results that light can be stored within the micro-cavities [6], micro-sphere [7] and nano-waveguide [8]. The promising concept is that white light, i.e. continuous light spectra can be generated, amplified and stored within a nano-waveguide, which is allowed to raise the concept of storing a narrow light pulse, i.e. a narrow spectral width. This is suitable for high resolution measurement in terms of optical resonant wavelength, whereas the measurement resolution of picometers(pm) or femtometer(fm) can be achieved. Many earlier works of soliton applications in either theory or experimental works are found in a soliton application book by Hasegawa et al. [9]. Many of the soliton related concepts in fiber optic are discussed by Agarwal [10]. The problems of soliton-soliton interactions [11], collision [12], rectification [13] and dispersion management [14] are required to solve and addressed. In practice, the soliton-soliton interaction would affect the dense wavelength division multiplexing (DWDM), however, this problem can be solved by using the suitable free spectrum range arrangement, which can be designed [15]. To present this concept, the use of optical soliton in nanoring resonator is formed with the large bandwidth signal, which can be compressed, filtered and stored within a nano-waveguide. Finally, the different resonant signals with different wavelengths are stored via the specific nano-waveguides in the array waveguide, which is available for sensing applications. The changes in physical quantities relating to the device parameters are observed and seen on the spectrum analyzer. The measurements of the related parameters with respect to the change in each wavelength can be performed by the distributed or multiplexed sensors. Quantum metrology using the present system is also described.